2015
DOI: 10.3109/08958378.2015.1037029
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells attenuate phosgene-induced acute lung injury in rats

Abstract: Accidental phosgene exposure could result in acute lung injury (ALI), effective therapy is needed for the patients with phosgene-induced ALI. As a type of cells with therapeutic potential, mesenchymal stem cells (MSCs) have been showed its efficacy in multiple diseases. Here, we assessed the therapeutic potential of MSCs in phosgene-induced ALI and explored the related mechanisms. After isolation and characterization of rat bone marrow MSCs (BMMSCs), we transplanted BMMSCs into the rats exposed to phosgene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
1
15
3
Order By: Relevance
“…In a rodent model of radiation-induced pulmonary fibrosis, administration of MSCs preserved the architecture of irradiated lungs, and this was partly mediated by endogenous expression of HGF 70 . Repair of the pulmonary blood-air barrier in a rodent model of phosgene-induced lung injury has also been shown to be mediated by MSCs 71 .…”
Section: Regeneration and Repairmentioning
confidence: 99%
“…In a rodent model of radiation-induced pulmonary fibrosis, administration of MSCs preserved the architecture of irradiated lungs, and this was partly mediated by endogenous expression of HGF 70 . Repair of the pulmonary blood-air barrier in a rodent model of phosgene-induced lung injury has also been shown to be mediated by MSCs 71 .…”
Section: Regeneration and Repairmentioning
confidence: 99%
“…Previous studies have shown that BMSCs, LRMSCs and hCMSCs play protective roles in lung injury caused by mechanical ventilation injury, endotoxin and plateau factors [6,8]. Other studies have reported that BMSCs can improve the lung injury caused by phosgene [4]. In this study, the roles of LRMSCs and hCMSCs in phosgene poisoning were con rmed and the effects of BMSCs, LRMSCs and hCMSCs in the same disease were compared.…”
Section: Discussionmentioning
confidence: 88%
“…BMSCs have a speci c role in the treatment of multiple systemic diseases such as acute pancreatitis, ischemic stroke, brotic scar and so on [1][2][3]. Previous studies have con rmed that BMSCs had decreases the severity of lung injury caused by phosgene [4]. LRMSCs are a class of MSCs derived from the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Various causes of lung diseases may inflict damage on lung blood-air barrier function, thereby affecting the respiratory function of the lungs (41,42). However, barrier disruption differs with injury type.…”
Section: Perturbing Effects Of Seawatermentioning
confidence: 99%